MAKNA “CELANA” DALAM KUMPULAN PUISI “SELAMAT MENUNAIKAN IBADAH PUISI” KARYA JOKO PINURBO - Abdullah, Risen Dhawuh (MIMESIS, 2023)
This research seeks to dismantle the philosophical meaning of "celana" from various points of view in the collection of poetry Selamat Menunaikan Ibadah Puisi by Joko Pinurbo. As for the poems that were carefully selected, only three poems contained the diction "celana", namely “celana, 1”, “celana, 2”, and “celana, 3”. The approach used was Paul Ricoeur's Hermeneutic Approach. This approach is used to obtain various philosophical meanings of "celana" in more depth. The chosen method is a qualitative-descriptive method with repeated reading techniques. Then the findings of this research is the philosophical meaning of "celana" which includes three meanings. First "celana" in the real context, "celana" as achievements in the context of education, "celana" as provisions in the context of religiosity.